Odpowiedzi

  • Użytkownik Zadane
2010-01-14T20:38:37+01:00
A) 3(a-2) = 3a - 6 = 3a + (-6)
b) -4(x+y) = -4x - 4y = -4x + (-4y)
c) -5(-x+1) = 5x - 5 = 5x + (-5)
d) -3a(¹₃ -a ) = -a + 3a²
e) (t-2s-1) 7 = 7t - 14s - 7 = 7t + (-14)s + (-7)
f) ¹₂(2a-4b+1) = a - 2b + 1/2 = a + (-2)b + 1/2
g) m(2m+3) = 2m² + 3m
h) 3p(2r+5p-1) = 6pr + 15p² - 3p = 6pr + 15p² + (-3)p
i) xy(2x-3y+5) = 2x²y - 3xy² + 5xy = 2x²y + (-3)xy² + 5xy
Najlepsza Odpowiedź!
  • Sunn
  • Rozwiązujący
2010-01-14T20:38:56+01:00
A) 3(a-2)= 3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(¹₃ -a )=-a+3a (kwadrat)
e) (t-2s-1)<razy> 7= 7t-14s-7
f) ¹₂(2a-4b+1)=a-2b+¹₂
g) m(2m+3)= 2m(kwadrat) +3m
h) 3p(2r+5p-1)= 6 pr + 15p(kwadrat)-3p
i) xy(2x-3y+5)=2x(kwadrat)y-3xy(kwadrat)+5xy
2010-01-14T20:43:43+01:00
A)3a-6
b)-4x-4y
c)5x-6
d)-a+3a a-do kwadratu
e)7t-14s-7
f)a-2b+1/2
g)2m(m-do kwadratu)+3m
h)6pr+15p(p-do kwadratu)-3p
i)2xy(x-do kwadratu)-3xy(y-do kwadratu)+5xy